Penegakan Hukum terhadap Pembajakan Hak Cipta Film dengan Media Internet Berdasarkan UU No. 28 Tahun 2014 tentang Hak Cipta - Theosalim, Alicia Salsabila (Syntax Literate, 2023)
Copyright is an exclusive right that arises when a work is published and is declarative in nature. Film creative works are the works that are most often pirated and are easily accessed via internet sites and this has a negative impact on creators, there are already regulations regarding copyright but there is still a lot of film piracy via the internet as a result of low public awareness regarding copyright. a masterpiece. This research was conducted using the normative legal method with a statutory regulation approach.